CONFLICTS FROM THE PERSPECTIVE OF ECONOMIC THEORY AND A HUMAN RIGHTS APPROACH TO EDUCATION - Nascimento, Julio Cesar (Seven Editora, 2026)
Education is an interdisciplinary subject influenced by several approaches to its understanding. In this perspective, this work aims to discuss education from the perspective of human rights and orthodox economics, highlighting them in the following points: 1. Treatment/point of education; 2. Objective/Purpose of education; 3. Functions of the State and market in education; 4. The educational system and; 5. Investments/Financing in education. The research was carried out taking into account International Covenants on Human Rights that treat education as a human right and works by authors of the orthodox economic approach that starts from the understanding of education as human capital, in which the main objective is to generate positive externalities, that is, returns. As a result, it is clear that there is a conflict in the five aforementioned points about education between the approaches. It is concluded that the treatment of economics on human rights is in conflict with the ideal of education as a human right.